VARIABEL YANG MEMPENGARUHI CITRA PRODUK FOOD SUPPLEMENT - Nina Septina (Center for Economic Studies Universitas Katolik Parahyangan, 2000)
Consumer's buying decision process influenced by many variables. One of them is product image. The product image cannot stand alone itself, but influenced by consumer's characteristic, such as sex, age, education level, occupation, and, income level. A research has done in order to get accurate information about how these characteristics influence the product image. The result of this research can be used by any company which involve in offering product food supplement.